The relevance of images. Patriarchal aesthetic construction in the television series The handmaid’s tale - Giménez Mateu, Francisco (Comunicación y Género [Communication and Gender], 2021)
The following paper is structured in three parts that come together with the same conclusion: the need to rethink the images, which in fact say much more than it may at first appear. Firstly, there will be a brief introduction to feminism, understood as a criticism of patriarchy. After this, we will try to demonstrate the importance of reading and understanding the images that are presented to us in our daily life. Nowadays images, undoubtedly, are the most important form of media that we use and we cannot let them just pass, without questioning them. To conclude, taking as example some images of the pilot episode of the television series The Handmaid’s Tale, we will carry out an interpretive audiovisual analysis in which we will try to reveal the power behind the images, everything that they can convey, even without realizing it, and everything that they can provoke in us.